2015
DOI: 10.3389/fnagi.2015.00126
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic cytokines as therapeutic players in early stages Parkinson’s disease

Abstract: Parkinson’s disease (PD) is a devastating age related neurodegenerative disease that is believed to have a lengthy prodromal state. It is critical to find methods to harness compensatory recovery processes in order to slow or prevent the eventual progression of clinical symptoms. The current perspective paper argues that immune system signaling molecules represent such a promising therapeutic approach. Two cytokines of interest are granulocyte macrophage-colony stimulating factor (GM-CSF) and erythropoietin (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 36 publications
1
14
0
1
Order By: Relevance
“…In this study we used a relatively low dose of 6-OHDA to induce a partial nigrostriatal lesion, which we believe may partially model a prodromal-like PD state. We have recently found that this animal model causes modest striatal lesions, coupled with morphological abnormalities of surviving neurons [ 5 ]. In the present study, we found that PC lipid species were markedly altered in animals treated with 6-OHDA.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study we used a relatively low dose of 6-OHDA to induce a partial nigrostriatal lesion, which we believe may partially model a prodromal-like PD state. We have recently found that this animal model causes modest striatal lesions, coupled with morphological abnormalities of surviving neurons [ 5 ]. In the present study, we found that PC lipid species were markedly altered in animals treated with 6-OHDA.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, previous studies have reported that PC lipids modulate anti-inflammatory signaling [ 17 ]. Moreover, it is known that 6-OHDA can induce microglial reactivity [ 5 , 18 , 19 ] and elevations of pro-inflammatory cytokines [ 20 , 21 , 22 ]. Thus, the decrease in PC lipids currently observed may influence cell survival in the context of 6-OHAD treatment by influencing inflammatory processes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations